PENERAPAN METODE MURAJA’AH DALAM MENINGKATKAN KWALITAS HAFALAN AL-QUR’AN DI PONDOK PESANTREN AN-NUR 3 MURAH BANYU TAHFIDZUL QUR’AN BULULAWANG - Alif Achadah, Hasan Bisri, Mazidatul Imamiyah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2024)
This research is motivated by students who follow tahfidz the majority are still in formal school and are still early, so how are the efforts of the management (ustadz/ustadzah) to offend the program by applying the murajaah method to make it easier for students to maintain and improve the quality of memorization of the Qur'an and get maximum results. While improving the quality of memorization which is the benchmark, namely the fluency of memorization that has been deposited. The results of this study can be known The application of the muraja'ah method in improving the quality of memorization of the Qur'an is that there are three categories of students when depositing memorization including takhassush, tafaqquh, and talathuf and there are supporting activities, namely muraja'ah kubro, Qiyamul lail 2 sheets, and tasmi 'bil hifdzi. Improving the quality of memorization of the Qur'an can be seen from several achievements/improvements in the quality of students in memorizing the Qur'an. Santri feels more enthusiastic and motivated to be more active in good and true muraja'ah in terms of makhraj and tajweed so that it is easy to find out the location of mistakes and the fluency of old memorization and new memorization. One of the inhibiting factors in the application of the muraja'ah method is the verses that have been memorized forgotten again, lazy, fatigue, and environmental conditions. Factors supporting the application of the muraja'ah method include caregivers, directors of the Qur'an tahfidzul program, administrators, ustadzah (caravans), and parents of students who with their support, motivation, and guidance can make quality hafidzah.